2019
DOI: 10.1097/jcp.0000000000001071
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Dynamics Effect of Serum Insulin-Like Growth Factor I and Cortisol/Dehydroepiandrosterone Sulfate Ratio on Symptom Severity of Major Depressive Disorder

Abstract: Background Insulin-like growth factor I (IGF-I) is a neurotrophic factor produced by the hypothalamic-pituitary-somatotropic axis and is considered a potential contributor to the pathology of major depressive disorder (MDD). Although it is known that the hypothalamic-pituitary-adrenal axis and cortisol are involved in the pathology of MDD, the association with dehydroepiandrosterone sulfate (DHEAS) remains unclear. The current study sought to clarify the relationship between these hormones and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
2
7
2
Order By: Relevance
“…An animal model research has proved that the supplement of DHEA could promote the proliferation of the granulosa cell and then stimulate the initiation of primordial follicles and the development of gonadotrophin-responsive preantral and early antral follicles [22]. In addition, oral DHEA supplement has been proved to upregulate the concentration of IGF-1 in serum [24], which is well known, and has a beneficial effect on follicular development and oocyte quality. is indicates that the positive effect of DHEA may be modulated by the increase of IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…An animal model research has proved that the supplement of DHEA could promote the proliferation of the granulosa cell and then stimulate the initiation of primordial follicles and the development of gonadotrophin-responsive preantral and early antral follicles [22]. In addition, oral DHEA supplement has been proved to upregulate the concentration of IGF-1 in serum [24], which is well known, and has a beneficial effect on follicular development and oocyte quality. is indicates that the positive effect of DHEA may be modulated by the increase of IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data collected on the role of neurotrophines in the pathophysiology of bipolar disorder has increased, they are conflicting and far from being sufficient [12]. Moreoever, it is argued that these neurotropic factors also change in other psychiatric diseases such as major depression and schizophrenia, which implies that the change in these factors may not be unique to bipolar disorder [37,38]. In order to reveal this point, we kept cortisol level, BMI and age under control statistically in the groups and we found that GDNF and Nrn 1 levels were significantly lower while IGF-1 levels were significantly higher in bipolar manic episode patients compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As of February 2017, we had recruited 91 patients with MDD for an initial study, which showed serum cortisol and IGF-1 levels were associated with symptom severity in patients with MDD 40 . Subsequently, as of March 2020, we had enrolled 54 male patients with MDD and 37 healthy male volunteers in a second study, which found serum IGF-1 levels were significantly higher in patients than in controls 41 .…”
Section: Methodsmentioning
confidence: 99%
“…These studies included a total of 107 patients with MDD and 37 healthy male volunteers. The current study extended the observation period and recruited additional participants including 71 patients with schizophrenia who were not included in our previous studies 40 , 41 . Of the participants in our previous studies, 84 patients (61 males and 23 females) with MDD and 35 healthy male individuals were included in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation